Povezanost mladostnikovega vedenjskega odnosa s starši in do šole z vedenjskim odstopanjem v zgodnji adolescenci - Milivojević Krajnčič, Antonija (Revija za elementarno izobraževanje, 2008)
My research work deals with the differences in behaviour among adolescents, the perception of their relationship with their parents and their attitude towards school during adolescence. The research work dealt with answering questions concerning the relationship with parents, attitude towards school and deviations in the behaviour of adolescents. Opačič (1995) argues that the relationship between parents, the environment and teenagers is not so important. He emphasizes the importance of their perception of such relationships. We used quantitative research procedures in our study. The study consisted of four different non-standardized questionnaires: (1) The frequency of behaviour deviation (2) The relationship with the mother and the relationship with the father (3) Conflicts with the parents connected with different conversation themes (4) Attitude towards school. The study relied on descriptive and causal-non-experimental methods of empirical pedagogical research. The research included a random sample of 7th and 9th grade pupils from a primary school in Maribor (n=300). The research was conducted during the 2007 school year.
Keywords: adolescenca; mladostniki; vedenjska odstopanja; vedenje; starši; medosebni odnosi; konflikti